(untitled) (LACCEI, 2024)
The purpose of the research is to determine the influence of information technology (IT) on the profitability of service companies (including educational institutions), considering the moderating effect of the explanatory variables investment in training, investment in knowledge management and the administrative practices. The study is non-experimental, with a correlational scope and a quantitative approach. Secondary data sources were used, obtained through official databases, from the year 2011 to 2017. The study presents an analysis of panel data from a Cobb-Douglas production function and regression models for the long term analysis. The results show that investment in IT positively influences profitability and that knowledge management plays the role of moderating variable in the short and long term.